Twitter sebagai Medium yang Berpotensi Bagi Organisasi: Mengonstruksikan Pesan Hijau di Twitter - Tangguh Okta Wibowo; Khairul Syafuddin; Maria Advenita Gita Elmada (Jurnal Riset Komunikasi (JURKOM), 2023)
This study examines the topic of environmental sustainability, which is currently emphasized by governments and organizations. How do organizations, in particular, utilize the term "green" to designate their products and services? A green label plays a crucial role in establishing a favorable reputation for an organization, allowing it to be identified as a promoter of environmental sustainability. This study explores the utilization of the green concept on Twitter deeper. Utilizing the Netlytic program, tweets containing the terms "green" or "environmental" are submitted to a content analysis. This study shows, using collected data, that Twitter is utilized as a "technology weapon" to promote the organization's image. By accommodating digital traces by users on Twitter, researchers see a "digital space" formed to be utilized as a space for organizations to produce content based on environmental communication. This information has consequences for the green labeling of an organization and enables the enhancement of a good image that adds value to the organization's reputation to establish itself as a pro-environmental organization. Important findings from this study suggest that Twitter could be utilized by organizations to improve their status on the map as a green organization.